A one‐step matrix application method for MALDI mass spectrometry imaging of bacterial colony biofilms. (23rd September 2016) - Li, Bin; Comi, Troy J.; Si, Tong; Dunham, Sage J. B.; Sweedler, Jonathan V.
Abstract : Matrix‐assisted laser desorption/ionization imaging of biofilms cultured on agar plates is challenging because of problems related to matrix deposition onto agar. We describe a one‐step, spray‐based application of a 2, 5‐dihydroxybenzoic acid solution for direct matrix‐assisted laser desorption/ionization imaging of hydrated Bacillus subtilis biofilms on agar. Using both an optimized airbrush and a home‐built automatic sprayer, region‐specific distributions of signaling metabolites and cannibalistic factors were visualized from B. subtilis cells cultivated on biofilm‐promoting medium. The approach provides a homogeneous, relatively dry coating on hydrated samples, improving spot to spot signal repeatability compared with sieved matrix application, and is easily adapted for imaging a range of agar‐based biofilms. Copyright © 2016 John Wiley & Sons, Ltd.